2004
DOI: 10.1111/j.1523-1755.2004.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic and nonhematopoietic potentials of Hoechstlow/side population cells isolated from adult rat kidney

Abstract: These findings implicate that Hoechst(low) cells in the kidney may have potentials for hematopoietic and nonhematopoietic lineages, but are not stem cells for renal cells, especially mesangial and tubular cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 36 publications
1
71
1
1
Order By: Relevance
“…The observation of cells with the same efflux profile in solid organs has raised the possibility of organ-based SP, which also may represent stem cells. Several groups have reported the existence of an SP in the adult rodent kidney (53)(54)(55)(56)(57). These data remain contradictory in terms of the relative size, origin, and lineage capacity of the renal SP.…”
Section: Renal Adult Stem Cellsmentioning
confidence: 79%
See 1 more Smart Citation
“…The observation of cells with the same efflux profile in solid organs has raised the possibility of organ-based SP, which also may represent stem cells. Several groups have reported the existence of an SP in the adult rodent kidney (53)(54)(55)(56)(57). These data remain contradictory in terms of the relative size, origin, and lineage capacity of the renal SP.…”
Section: Renal Adult Stem Cellsmentioning
confidence: 79%
“…These data remain contradictory in terms of the relative size, origin, and lineage capacity of the renal SP. Iwatani et al (55) showed no evidence for a capacity to transdifferentiate into renal cells in vivo. Hishikawa et al (54,56) reported that these cells possess renal and multilineage capacity in culture.…”
Section: Renal Adult Stem Cellsmentioning
confidence: 99%
“…8 Iwatani et al reported that kidney SP cells represented 0.03-0.10% in adult rat kidney and the cells showed hematopoietic potential. 9 Asakura et al reported that kidney SP cells are approximately 5% of all cells in mice and the cells are likely bone marrow-derived hematopoietic stem cells. 10 In this report, for the first time, we optimized the condition for human kidney SP analysis and confirmed the existence of SP cells (1.3%) in human kidney.…”
Section: Resultsmentioning
confidence: 99%
“…4 They also reported that the activation of kidney SP cells by inhibition of histone deacetylase reversed chronic renal failure. 9 However, the infused kidney SP cells into kidney with acute renal injury have not been proved to differentiate into renal cells. 4,5 In this issue of the Journal, Inowa et al report the isolation of human SP cells from the kidney.…”
Section: Editorial Commentmentioning
confidence: 99%
“…[33][34][35][36] These cells have been shown to comprise approximately 0.03-0.1% of the kidney cells. 34 The isolated cells have mixed cell populations containing cells of bone marrow and renal origin, and, using these indirect methods, investigators have demonstrated an interstitial and tubular niche for SP cells.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%